GLOBAL RANKINGS AND THEIR IMPACT ON EDUCATION QUALITY - Sharifova, Irina (Журнал иностранных языков и лингвистики, 2025)
Global university rankings have become a dominant feature in the higher education landscape, shaping institutional strategies, public perception, and policy decisions. While rankings aim to provide benchmarks of quality, their methodologies often prioritize research output, international visibility, and reputation over teaching quality and student experience. This article explores the multifaceted impact of global rankings on higher education quality. It examines how institutions adapt to ranking criteria, sometimes at the expense of broader educational missions such as equity, access, and holistic student development. The paper also considers whether rankings genuinely reflect educational quality or merely reinforce global hierarchies. Findings highlight both the opportunities—such as increased competitiveness, international collaboration, and accountability—and the challenges, including overemphasis on metrics, neglect of local contexts, and pressures on faculty and students. The article concludes that while global rankings can drive improvement in certain areas, they should not be considered the sole indicator of higher education quality, and more comprehensive, context-sensitive approaches are needed.